Analysis Kesesuaian Pengembangan Wisata Bahari Berkelanjutan di Pantai Jemeluk, Amed, Kabupaten Karangasem, Bali - Juliyah Emka; I Wayan Restu; Suprabadevi Ayumayasari Saraswati (Program Studi Manajemen Sumberdaya Perairan, Fakultas Kelautan dan Perikanan, Universitas Udayana, 2020)
The diversity of biodiversity in Jemeluk Beach did not guarantee that all marine tourism activities on Jemeluk Beach was not have damage or negative impact on the environment. This research was conducted to determine how the suitability of marine tourism conditions (snorkeling, diving, and beach recreation) in an effort to preserve sustainable marine tourism. This research used the analysis of tourism suitability by comparing the characteristics and quality of land against land use requirements for certain tourism activities. The method of measuring coral cover used the LIT (Line Intercept Transect) method which is based on the form of coral growth. Measurement of the type and number of reef fishes was assessed using the UVC (Underwater Visual Cencus) method by taking data along 50 meters at the same depth as the coral cover data collection. The suitability condition of snorkeling tourism at points I and II was classified as quite appropriate with a value of 78% and 72.23%, while point III was classified as conditionally appropriate with a value of 46.3%. The suitability of diving tourism at points I and II were classified as conditional according to the values of 44.5% and 38.2%, while point III was classified as incompatible with the value of 33.34%. While the results of the calculation of the suitability of the beach tourism index showed a very suitable category with a value of 90% to be used as an object of marine tourism development.